One-step construction of aminosquaraine backbone. (August 2016) - Ying, Hanze; Cheng, Jianjun
Abstract: One-step construction of the amino-substituted squaraine dye backbone was discovered unexpectedly in an amidation reaction. Under the catalysis of Mukaiyama's reagent, (4-dimethylamino)phenylacetic acid and bulky secondary amine 2, 2, 6, 6-tetramethylpiperidine give the reduced form of aminosquaraine instead of amide as the major product. The reduced form of aminosquaraine can be oxidized to a dark-colored conjugated aminosquaraine within seconds. The method provides a novel and facile way to functionalize the four-membered core of squaraine dye. Graphical abstract: Highlights: Amidation reaction unexpectedly gives reduced aminosquaraine as the major product. Reaction mechanism and substrate requirement are proposed and studied. The reduced aminosquaraine can be facilely oxidized to conjugated aminosquaraine.